Occupational musculoskeletal disorders in female workforce: a bibliometric perspective - Bayu Yoni Setyo Nugroho; Izzatul Alifah Sifai; Ratna Setyaningrum; Muhammad Dyas Husnan Khair (Universitas Gadjah Mada, 2026)
Purpose: To conduct the first gender-sensitive bibliometric analysis of work-related musculoskeletal disorders (WMSDs) among female workers using Web of Science data (1999–2025), addressing a critical gap in occupational health research. Methods: A bibliometric methodology was applied to 59 scholarly articles extracted from the Web of Science (WoS) Core Collection (1999–2025), selected from an initial pool of 1,847 records via systematic screening based on subject area, language, document type, and gender-specific occupational focus. VOSviewer (version 1.6.20) and R Bibliometrix (version 4.x) were employed for co-citation analysis (citation threshold = 1, yielding 54 cited references) and keyword co-occurrence analysis (67 keywords; total link strength = 327). Results: Eight research clusters were identified: Clinical Conditions and Pain and General Health and Work Environment emerged as the most dominant clusters, followed by Risk Assessment and Demographics, Anatomical Regions and Specific Disorders, Work Conditions and Psychosocial Factors, Physical Demands and Ergonomics, Prevalence and Epidemiology, and Intervention and Management. Publications remained low from 1999 to 2010 but increased markedly from 2011, peaking at 9–10 articles per year in 2020–2021. Citations grew exponentially from 2015, exceeding 130 annually in 2021. Public Environmental Occupational Health dominated the field (50% of studies; 787 total citations; 29.15 citations/year). Conclusion: This study provides the first bibliometric mapping of occupational MSDs in female workers, revealing critical gaps in female-specific ergonomic and psychosocial interventions (Cluster 8). These findings highlight the urgent need for gender-sensitive workplace policies, targeted ergonomic guidelines, and gender-disaggregated risk standards in labor frameworks—particularly within female-dominated sectors like garment manufacturing, food processing, and healthcare.